23.2k views
3 votes
2/3 - 3/2y + 1/3y + 4 = 0​

User Beluga
by
6.0k points

2 Answers

4 votes

Answer:

y = 4

Explanation:

Please use parentheses for clarity, remembering what big differences they make in expression values.

I will assume that your "2/3 - 3/2y + 1/3y + 4 = 0​" actually means

2/3 - (3/2)y + (1/3)y + 4 = 0​

The LCD here is 6, which is the product of the denominators 2 and 3.

Then your "2/3 - 3/2y + 1/3y + 4 = 0​" becomes:

4 - 9y + 2y + 24 = 0, which simplifies to:

28 - 7y = 0. Solving this, we get y = 4

User Elliot Gorokhovsky
by
5.4k points
4 votes

Answer:

y = 4

Explanation:

(2/3 + 4) + (-3/2y + 1/3y) = 0

(-3/2y + 1/3y) = -4 2/3

-9/6y + 2/6y = -14/3

-7/6y = -14/3

cross-multiply:

-21y = -84

y = 4

User Mahdikmg
by
4.8k points